Improvement of process of forming of tariffs on the enterprises of housing and communal services as an element of modernization - Bella Sheleheda (Cхід)
The problem aspects related to determination of economically reasonable tariffs on services of housing and communal services are considered in the article, sparing the special attention to the improvement of process of forming of tariffs as element of modernization. Actuality of application of method of profitability of the invested capital that stimulates the wave of investments and avouches for the investors of return and market profitability of the inlaid facilities is determined.